Factors Associated With Early Menopause In Dukuh Village Indramayu District In 2021 - Tutin Marlia (Institute of Computer Science (IOCS), 2023)
Menopause is an ubiquitous aspect of reproduction. Due to hormonal fluctuations that occur during menopause, a variety of physical and mental symptoms might be observed. Some pre-elderly women in Muntur Village, Losarang District, Indramayu Regency in 2021 are prepared for menopause, while others are not. Symptoms range from minor to severe on the physical and psychological fronts. 34 respondents (52.3%) reported mild bodily changes, 22 respondents (33.8%) experienced moderate physical changes, and 9 respondents (13.8%) suffered severe physical changes, according to the findings. 17 respondents (26.2%) reported no anxiety, 28 respondents (43.1%) reported mild anxiety, 19 respondents (29.2%) reported moderate anxiety, and 1 respondent (1.5%) reported severe anxiety. Thirty respondents (46.2%) were prepared for menopause, whereas thirty-five respondents (53.8%) were not. Chi-square p = 0.016 indicates a significant link between physical changes in responders and preparation to face menopause in pre-elderly persons in Muntur Village, Losarang District. Chi Square p = 0.018 indicates a strong association between anxiety levels and preparedness for menopause in Muntur Village, Losarang District.